Strategising for culinary tourism (CT) success - Ali, Norhidayah; Andin Salamat, Azni Syafena; Abu Bakar, Suhaida (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
Culinary or food is inextricably linked with culture, as it contributes to the birth of numerous cuisines. When tourists travel to a new place, they often wish to be immersed in the local experience, and cuisine is an integral part of the experience. Sampling authentic local dishes allows visitors to be fully immersed in the destination's culture and traditions. For those embarking on a culinary tourism (CT) adventure, they look forward to experiencing a delicious fusion of flavours and cultures. As the world's demand for gastronomic adventures keeps growing, most businesses feel that success in this profession requires mastering the art of strategy. Culinary tourism, also known as food tourism or gastronomy tourism, is seen as a way of exploring a destination through its food and beverage offerings. This type of tourism focuses on authentic local foods, usually characterised by visits to markets, street food stalls, and traditional restaurants to experience regional specialities (Long, 2014). Culinary tourism offers a mouthwatering assortment of experiences, especially for tourists, from enjoying gourmet dining at high-star-rated restaurants to relishing unusual street delicacies in vibrant markets. Culinary tourism has been extensively studied in neighbouring countries such as Thailand and Indonesia (Kattiyapornpong et al., 2021; Wijaya et al., 2021). However, this field of research remains limited in Malaysia. Therefore, studying local food attributes and contents is crucial to fill in the gaps in the marketing aspects and, simultaneously, aid the hospitality and tourism providers in understanding the needs and wants of the tourists regarding the local cuisine (Sanip et al., 2022). In this paper, we explore the crucial tactics or strategies that lead to the success of culinary tourism, revealing the fundamental components for a gratifying and rewarding culinary journey. Successful tactics or strategies can provide tourists with a memorable and authentic experience, considerably increasing destination appeal and visitor satisfaction. These tactics and strategies also encourage local culture and food, which can spill into economic growth and sustainability in the community.